2012
DOI: 10.3758/s13423-012-0264-4
|View full text |Cite
|
Sign up to set email alerts
|

A feature-inversion effect: can an isolated feature show behavior like the face-inversion effect?

Abstract: The face-inversion effect (FIE) is explained by the configural-processing hypothesis. It proposes that inversion disrupts configural information processing (spatial links among facial features) and leaves the processing of featural information (eyes, nose, and mouth) comparatively intact. According to this hypothesis, an inverted isolated facial feature cannot show a feature-inversion effect-that is, behavior similar to the FIE-since all the spatial links between it and the other features in a face are elimina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…This proposal, which may be viewed as the "extended configural-processing" hypothesis, can handle Rakover and Teucher's (1997) findings by pointing out that for face processing, the spatial relations within a facial feature are no less important than those between features. Rakover (2012) found empirical support for the extended configural-processing hypothesis in a same/different experimental procedure: Recognition of isolated eyes was better when they were upright rather than inverted; that is, recognition of isolated eyes showed behavior similar to the face (UI) effect. Furthermore, perception and recognition of eyes tilted downward and upward (a within configural information change) were better when the eyes were upright rather than inverted.…”
Section: A Necessary and A Sufficient Conditionmentioning
confidence: 65%
See 1 more Smart Citation
“…This proposal, which may be viewed as the "extended configural-processing" hypothesis, can handle Rakover and Teucher's (1997) findings by pointing out that for face processing, the spatial relations within a facial feature are no less important than those between features. Rakover (2012) found empirical support for the extended configural-processing hypothesis in a same/different experimental procedure: Recognition of isolated eyes was better when they were upright rather than inverted; that is, recognition of isolated eyes showed behavior similar to the face (UI) effect. Furthermore, perception and recognition of eyes tilted downward and upward (a within configural information change) were better when the eyes were upright rather than inverted.…”
Section: A Necessary and A Sufficient Conditionmentioning
confidence: 65%
“…In these cases, the visual system processes seem to take over, the feature becomes salient-an attention attractor-and the effect of inversion disappears. Similarly, Rakover (2012) found that perception and recognition of the eyes (within the whole face or in isolation) in upright and inverted positions were the same when the irises were blackened. In the same vein, focusing attention on a local area in the face reduces the effect of inversion (e.g., Barton et al, 2001;Tanaka & Gordon, 2011).…”
Section: Fsi Model and Facial Informationmentioning
confidence: 99%
“…The absence of a LVF/RH advantage with inverted faces we reported here is consistent with previous evidence indicating that inversion is specifically detrimental for configural modes of face processing (cf. Leder & Carbon, 2006;McKone & Yovel, 2009;Rakover, 2012). In fact, prior findings collected with cataract reversal patients using the same face set as that used here (Le Grand et al, 2001;Robbins et al, 2010) showed that inversion particularly disrupts a configural mode of processing that seems to be specific for human faces presented in their standard upright orientation; a process that is not employed for other faces such as animals (e.g., monkeys) or objects (e.g., houses).…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, several previous studies employing a sequential same-different face-matching task investigating featural versus spacing processing have selectively reported effects of experimental manipulations on accuracy measures (e.g., Keyes, 2012;Lobmaier et al, 2010;Pitcher et al, 2007;Rakover, 2012;Yovel & Kanwisher, 2008), suggesting that reaction times may be a less sensitive measure than accuracy measures in these kinds of tasks.…”
Section: Discussionmentioning
confidence: 99%
“…First, the task used in the current study was a passive viewing of upright and inverted faces and houses. Although previous behavioral studies showed that the inverted presentation of faces impairs configural processing of faces [Maurer et al, ], it is pointed out that the inversion also has an influence on the processing of facial parts [Doi et al, ; Rakover, ]. To determine functional roles of the IOG and the FG during an early stage of face processing, it would be favorable to manipulate facial parts and configuration separately [Liu et al, ] or to demand the processing of each aspect.…”
Section: Discussionmentioning
confidence: 99%